Psychotherapy system of psychoendocrine syndrome in the thyroid gland and the adrenal cortex pathology - V. V. Ischuk (Kazimierz Wielki University, 2016)
Ischuk V. V. Psychotherapy system of psychoendocrine syndrome in the thyroid gland and the adrenal cortex pathology. Journal of Education, Health and Sport. 2016;6(12):875-882. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.254506 http://ojs.ukw.edu.pl/index.php/johs/article/view/4187         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016.   PSYCHOTHERAPY SYSTEM OF PSYCHOENDOCRINE SYNDROME IN THE THYROID GLAND AND THE ADRENAL CORTEX PATHOLOGY   V. V. Ischuk   -                      Ukrainian Scientific-Practical Center of endocrine surgery, endocrine transplantation of organs and tissues of the Ministry of Health of Ukraine -                      androman2008@mail.ru -            Summary To study the clinical and psychopathological features and systematization-tion of psychopathological abnormalities in structure of psychoendocrine syndrome in patients with thyroid gland and adrenal cortex metabolism violation, a prospective study of 300 patients who were treatment on the basis of the Ukrainian Scientific-Practical Center of Endocrine Surgery, Transplantation of endocrine organs and the Ministry of Health of Ukraine tissues, was conducted. A questionnaire of identification of nozogenic psychotraumatization factors was created, as well as contranozogenic vector of psychotherapy system that uses research results as a factor of psychotherapeutical impact focusing. Key words: psychoendocrine syndrome, psychotherapy, psychotrauma, nozogenic factors.